Hayden White: a postsecular perspective. - Wiśniewski, Tomasz (Rethinking History)
In this article, I propose a postsecular reading of Hayden White's understanding of the figure and the 'figure-fulfilment model of narrativity'. I suggest that White revealed and set in motion intellectual resources that contested the superficially secular nature of historical thinking that would otherwise have remained undiscovered in the theory of history. My article is an attempt towards recognizing the potential that White's theory contains for analysing postsecular aspects of contemporary historical thought. It focuses on an analysis of the 'figure-fulfilment model of narrativity'. I term the phenomenon discovered by White the 'cryptotheology of the figure'. I believe that an analysis of White's works from various periods can provide insight into the 'secularization of the historical imagination'.